Categorical perception of emotional facial expressions in alcohol-dependence. (1st November 2015) - D'Hondt, Fabien; de Timary, Philippe; Bruneau, Yaelle; Maurage, Pierre
Highlights: Emotional decoding abilities were assessed in alcohol-dependent individuals (ADI). A morphing procedure was used to explore the categorical perception effect. Categorical perception of emotional facial expression per se is preserved in ADI. ADI exhibit an emotional decoding bias characterized by an under-identification. The emotional decoding of ambiguous stimuli is impaired among ADI. Abstract: Background: Emotional deficits have been widely described in alcohol-dependence, but several subtle and critical emotional decoding abilities remain to be investigated. In particular, the ability of alcohol-dependent individuals to process emotionally ambiguous facial stimuli, which are more frequent in everyday life than full emotional facial expressions, remains poorly understood. The present study used a categorical perception paradigm to evaluate the identification of mixed emotional facial expressions among alcohol-dependent participants. Method: Nineteen recently detoxified participants with alcohol-dependence and 19 healthy controls were presented with facial stimuli depicting four emotional facial expressions (happy, angry, sad, and neutral), morphed along continua between each possible pair of emotions. Participants had to indicate the predominant emotion within the randomly presented facial stimuli. For each emotional category, a logistic function that estimated the percentage of identification according to the morph steps was adjusted for each participant's data. Results: While there was no significant group difference regarding the response slope ( p  = 0.502, η p 2  = 0.014), the identification threshold was significantly increased in alcohol-dependent participants compared to controls ( p  = 0.007, η p 2  = 0.204), independently of the emotional category. Conclusions: The categorical perception of emotional facial expression per se appeared preserved in alcohol-dependence, but alcohol-dependent participants exhibited a bias in emotional facial expression decoding characterized by a global under-identification. This study is the first to evidence a deficit of alcohol-dependent individuals in the processing of ambiguous emotional facial expressions by using this emotional continuum paradigm measuring the categorical perception effect.